Impact of anti-slip socks on agility and speedperformance among male futsal players / Muhammad Atif Azamuddin Mohd Azmi... [et al.]. - Mohd Azmi, Muhammad Atif Azamuddin; Raja Hussain, Raja Nurul Jannat; Shari, Maisarah; Mohamed, Muhamad Noor; Mazaulan, Mardiana; Saiful Annur, Muhamad Safiq; Adnan, Mohd Aizzat; Abu Kassim, Nurul Ain; Md Radzi, Noor Azila Azreen (Universiti Teknologi MARA, Negeri Sembilan, 2025)
Footwear and socks play a crucial role in sports performance, particularly in agility and speed. Given the high incidence of ankle sprains in futsal, exploring ways to enhance stability is essential [1]. This study compares the effects of anti-slip socks and standard socks on agility and speed among UiTM Negeri Sembilan futsal players to determine their impact on performance. This experimental study involved 24 male UiTM Negeri Sembilan futsal players (aged 19–24). Speed and agility were assessed using the 30-meter sprint and Illinois agility test. Each participant completed both tests wearing standard socks first, with a 10-minute rest between trials. After a one-day recovery, the tests were repeated with anti-slip socks to compare performance differences.